A new species of the Liolaemus darwinii group (Iguania: Liolaemidae) from Salta Province, Argentina - Abdala, Cristian Simón; Quinteros, Andrés Sebastián; Arias, Federico; Portelli, Sabrina; Palavecino, Antonio (Zootaxa, 2011)
We describe a new species of the iguanian genus Liolaemus of Northwestern Argentina in Salta Province. This new lizard is a member of the L. boulengeri group, and within this group it is a member of the L. darwinii subgroup. With the addition of the species described here, the L. darwinii group now contains 19 species. Like most of the members of this group, the new taxon exhibits sexual dichromatism, showing a unique color pattern in males and females. The color pattern is characterized by the presence of a pre-scapular spot and lateral black stripes, unique within the L. darwinii group. Liolaemus diaguita sp nov inhabits a region where bushes are the predominant vegetation, in Quebrada de Las Conchas, in Guachipas Department, Salta Province, which has an elevation between 1200–2500 m.